2020
DOI: 10.1177/0098628320901384
|View full text |Cite
|
Sign up to set email alerts
|

APA-Style Citations Can Create a Roadblock to Textbook Comprehension for Less Skilled Readers

Abstract: We examined the effect of in-text American Psychological Association (APA)-style citations on quiz performance as a function of structure building ability, measured by the Multi-Media Comprehension Battery. Participants were randomly assigned to either APA or no citation conditions and asked to read an expository text followed by a comprehension quiz. Less skilled structure builders performed significantly lower on a comprehension quiz and read faster in the APA citation compared to the no citation condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The scientific writing skills of the experimental group increased in terms of writing properly, being free of common linguistic errors, avoiding bias, using scientific methods appropriately, and being able to apply the standards of organization and output in the scientific paper. Similar studies support these results (Al-Ahwal, 2015), (Al-Ahwal, 2016), (Hussein & Al-Mahlawi, 2018), (Hilali, 2019), (Khattab, 2020), (Stiegler-Balfour et al, 2020), (Al-Zahrani, 2021, and (Ibrahim, 2021), where these studies showed higher effectiveness of training programs in increasing the ability of scientific writing skills among study samples in favor of the post-test. Although they differ from other studies (Boysen, 2019); where this study showed no improvement in academic skills writing among the study sample.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The scientific writing skills of the experimental group increased in terms of writing properly, being free of common linguistic errors, avoiding bias, using scientific methods appropriately, and being able to apply the standards of organization and output in the scientific paper. Similar studies support these results (Al-Ahwal, 2015), (Al-Ahwal, 2016), (Hussein & Al-Mahlawi, 2018), (Hilali, 2019), (Khattab, 2020), (Stiegler-Balfour et al, 2020), (Al-Zahrani, 2021, and (Ibrahim, 2021), where these studies showed higher effectiveness of training programs in increasing the ability of scientific writing skills among study samples in favor of the post-test. Although they differ from other studies (Boysen, 2019); where this study showed no improvement in academic skills writing among the study sample.…”
Section: Discussionsupporting
confidence: 59%
“…The academic writing skills of postgraduate students at the College of Education were developed and the impact of this on their ability to write research plans was investigated, the positive effect of the training program on the skills required to write a research plan has been found (Khattab, 2020). Stiegler-Balfour et al (2020) studied the influence of in-text APA-style citations on quiz performance as judged by the Multi-Media Comprehension Battery's structure-building ability. The participants were randomly assigned to one of two conditions (APA or no citations) and asked to read an expository text, followed by a quiz on comprehension.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several general principles for effective multimedia use in e-learning have been identified. The reduction of extraneous processing (unrelated to subject material), the management of essential processing (directly related to subject material), and the fostering of generative processing (mental organization and knowledge integration) have been identified as important guiding principles for designing computer-based multimedia instructional materials (Mayer, 2017; Stiegler-Balfour et al, 2020; Sweller, 2020; Tugtekin & Odabasi, 2022). These processing types have an overall goal of keeping students’ cognitive load to a manageable level, so as to not overload while simultaneously maintaining interest and desirable challenge.…”
Section: Cognitive Load and Digital Learningmentioning
confidence: 99%